Antimicrobial resistance in Campylobacter species isolated from commercially sold steak (beef) and raw cow milk in Abakaliki, Nigeria - NNABUIFE BERNARD AGUMAH; MUSTOFA HELMI EFFENDI; ADIANA MUTAMSARI WITANINGRUM; WIWIEK TYASNINGSIH; EMMANUEL NNABUIKE UGBO; CHINEKWU SHERRIDAN NWAGWU; IFUNANYA AGATHA UGBO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Agumah NB, Effendi MH, Witaningrum AM, Tyasningsih W, Ugbo EN, Nwagwu CS, Ugbo IA. 2024. Antimicrobial resistance in Campylobacter species isolated from commercially sold steak (beef) and raw cow milk in Abakaliki, Nigeria. Biodiversitas 25: 950-956. This study aimed to ascertain antimicrobial resistance in Campylobacter species isolated from commercially sold steak (Beef) and raw cow milk in Abakaliki. Pools of milk samples and steak were bought at various outlets and analyzed using standard microbiological methods. Results showed that two species of Campylobacter, namely Campylobacter coli, were isolated from the samples. In raw cow milk, Campylobacter coli had a frequency of 65% higher than Campylobacter jejuni (20%). While in steak, C. coli was 34.53% higher than C. jejuni (19.10%). The antibiotic susceptibility profile for C. coli isolated from raw cow milk ranged from 61.54% to 100%, especially for trimethoprim and cephalexin. Resistance ranged from 0.00 to 38.46%. The highest resistance was recorded for tetracycline. The antibiotic susceptibility profile for C. coli isolated from steak recorded susceptibility values ranging from 60.53% to 86.84%. Cephalexin had the highest effect on C. coli isolates from steak. Resistance values ranging from 13.16% to 42.11% were recorded with Nalidixic acid as the least effective antibiotic. C. jejuni isolated from cow raw milk, susceptibility ranging from 0.00% to 100% was recorded, especially for Cefotaxime, Imipenem, Cephalexin, and Nalidixic acid. Resistance ranged from 0.00% to 100%, especially for Chloramphenicol and Kanamycin. For C. jejuni, susceptibility values ranged from 26.57% to 85.71%, with imipenem presenting the highest effect. Resistance values ranged from 23.81% to 71.43%. Gentamycin had the least effect. Adequate sanitation, personal hygiene, and appropriate use of antibiotics are highly recommended for food handlers and farmers to safeguard human health by reducing AMR challenges, even in milk and meat/meat products.